Numerical study of TRIP transformation in 35NCD16 steel-effects of plate orientation and some criteria - Mounir Gaci; Fedaoui Kamel; Lazhar Baroura; Amar Talhi (Fracture and Structural Integrity)
This study aims to analyze the effect of thermo mechanical coupling damage in the presence of a phase change (austenite/martensite) in 35NCD16 steel. The impact of increasing mechanical traction load, accompanied by a martensitic transformation on the scale of a single grain with boundary has been studied. The prediction transformation of induced plasticity (TRIP) was evaluated by taking into account the following parameters: twenty shear directions of the martensitic plates, two values of the shear deformation of the martensitic plates, energetic and thermodynamics criteria for getting in order the transformation of the martensitic plates, elastoplastic behavior of the two areas in the first case (martensitic plate and grain boundary) and elastic behavior for the grain boundary in the second case. The numerical calculation is carried out using the finite element method (FEM), implemented in the Zebulon calculation code. The developed approach is validated using the available experimental results reported in the literature. The numerical results showed that the estimation of TRIP given by the energetics criteria with the values of the shear deformation (γ0 = 0.16) are closer to the experiment results.